An engineered hydrogel with low-dose antitumor drugs enhances tumor immunotherapy through tumor interstitial wrap - Li, Zhongxian; Xiang, Jiawei; Zhang, Qiang; Zhao, Mingyuan; Meng, Yuan; Zhong, Jie; Li, Tingting; Jia, Lanxin; Li, Kai; Lu, Xi; Ao, Zhuo; Han, Dong (Frontiers in Bioengineering and Biotechnology, 2022)
Stimulating immunogenic cell death (ICD) is the key to tumor immunotherapy. However, traditional chemoradiotherapy has limited effect on stimulating immunity and often requires repeated administration, which greatly reduces the tumor-killing effect. In this article, we created a sodium alginate hydrogel sustained-release system containing low-dose doxorubicin (Dox) and immune adjuvant R837, which were injected into the interstitial space to wrap around the tumor in situ, achieving a sustained release and long-lasting immune response. Cooperating with immune checkpoint blockade, Dox induced ICD, activated dendritic cells (DCs) and converted immunosuppressive M2-type tumor-associated macrophages (TAM) to tumor-killing M1-type TAMs. Simultaneously, it greatly promoted T cell proliferation and infiltration, and reduced tumor immunosuppressive factors, triggering a robust immune response to suppress tumors in vivo. In conclusion, this anti-tumor strategy based on interstitial injection can achieve continuous local immune stimulation by low-dose chemotherapy drugs, providing a potential approach for tumor immunotherapy.